Plataforma para el aprendizaje electrónico (E-learning): un aporte a la formación continua en la educación superior - Lizeth Badillo Durán; Andrés Felipe Ditta Lobo; Juan Sebastián Castro Sánchez (Mundo Fesc)
Continuing education is a matter of vital interest in universities after obtaining a professional academic degree. The characteristics of development, learning, and monitoring of professionals are the greatest demand at the labor level for entities, because they allow good performance at the strategic level in terms of educational quality and competitive practice. The central objective was to achieve an effective system for promoting the continuing education of graduates through the use of digital educational resources. Therefore, the implementation of an electronic learning platform (E-Learning) was chosen for the improvement, teaching, and outreach of continuing education for professionals; based on a type of descriptive and applied research with a qualitative approach. The virtual platform was created using the (Metric II) methodology because it has a structure of procedures designed for the development of software in education; achieving the formulation of progress, effectiveness, and continuous training of graduates by managing digital learning content.